MC4R variants modulate α-MSH and setmelanotide induced cellular signaling at multiple levels - Alejandra Virginia Rodriguez Rondon; Mila S. Welling; Erica L T van den Akker; Elisabeth F. C. van Rossum; Elles M. J. Boon; Mieke M. van Haelst; Patric J. D. Delhanty; Jenny A. Visser (2024)
Abstract Context The melanocortin-4 receptor (MC4R) plays an important role in body weight regulation. Pathogenic MC4R variants are the most common cause of monogenic obesity. Objective We have identified 17 MC4R variants in adult and pediatric patients with obesity. Here we aimed to functionally characterize these variants by analyzing 4 different aspects of MC4R signaling. In addition, we aimed to analyze the effect of setmelanotide, a potent MC4R agonist, on these MC4R variants. Materials and Methods Cell surface expression and α-melanocyte stimulating hormone (α-MSH)- or setmelanotide-induced cAMP response, β-arrestin-2 recruitment, and ERK activation were measured in cells expressing either wild type or variant MC4R. Results We found a large heterogeneity in the function of these variants. We identified variants with a loss of response for all studied MC4R signaling, variants with no cAMP accumulation or ERK activation but normal β-arrestin-2 recruitment, and variants with normal cAMP accumulation and ERK activation but decreased β-arrestin-2 recruitment, indicating disrupted desensitization and signaling mechanisms. Setmelanotide displayed a greater potency and similar efficacy as α-MSH and induced significantly increased maximal cAMP responses of several variants compared to α-MSH. Despite the heterogeneity in functional response, there was no apparent difference in the obesity phenotype in our patients. Conclusion We show that these obesity-associated MC4R variants affect MC4R signaling differently yet lead to a comparable clinical phenotype. Our results demonstrate the clinical importance of assessing the effect of MC4R variants on a range of molecular signaling mechanisms to determine their association with obesity, which may aid in improving personalized treatment.